Business systems and societal context: comparing Chinese and Indian models - Grainger, Richard; Chatterjee, Samir (AMDISA PUBLICATIONS, 2007)
China and India, in terms of geography, population size and regional cultural influence, are the most important Asian nations. Both have experienced consistently high economic growth rates over the past decade and it is widely assumed they will have a profound global and regional impact on the 21st century. The potential of these two nations suggests that a comprehensive understanding of their business systems is vital for competitors, trading partners, and those who would learn from their development ecxperiences. An adaption of Redding's (2005) model is utilized for the purpose of describing, analyzing and comparing the business systems of China and India. It is important to note that this approach does not attempt to derive causality between societal factors and economic performance, but within the limited scope and constraints of this relatively short document, demonstrates how enhanced understanding might be achieved through the use of the proposed model.